The Study Of The Effectiveness Of The Inquiry Based Learning Method In Chemistry Teaching Learning Process - et. al., Jogendra Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This Research Is A Quantitative Study In Which Traditional Method Is Used In A Limited Way As Compare To Modern Teaching Method Like Inquiry Based Learning. The Aim Of This Study Was To Find Out Effectiveness Of Inquiry-Based Learning Method On Student's Achievement In Chemistry Lessons. A Total Of 80 Students Are Selected In Which 60 Are Rural And The Other 60 Are Urban In Jhunjhunu District. They Were Selected Through Purposive Sampling Methods, The Group Which Was Assigned As An Experimental Group Was Instructed Through Inquiry-Based Learning Methods And Another Group Was Traditionally Instructed. This Research Is An Experimental Study With Non-Proportional Groups. In Which The Pre And Post-Test Will Be Done With The Control Group And The Classes Will Be In The Form Of Control And Experimental Groups. It Is Concluded From Research That Inquiry Based Method Is Much More Effective Than Traditional Teaching Method In Both Urban And Rural Students.